Developing country-specific wheelchair service provision strategic plans for Romania and the Philippines. (18th August 2019) - Gowran, Rosemary Joan; Goldberg, Mary; Comanescu, Gabi; Ungureanu, Claudia; Garcia, Ferdiliza Dandah S.; Xavier, Cheryl Ann; Pearlman, Jon
Abstract: Background : Achieving appropriate wheelchair provision at a national level is complex, requiring regulations, funding and policies established through governments. Understanding wheelchair provision within different countries is key. This paper describes the process used to support the development of wheelchair service strategic plans in Romania and the Philippines. It considers the influences, meaning, challenges and developments when producing strategic priorities within two different contexts. Methods : The International Society of Wheelchair Professionals (ISWP) sponsored affiliates Motivation Foundation Romania and the Philippine Society of Wheelchair Philippine Society of Wheelchair Professionals (PSWP), to conduct organizational ethnographic mixed method stakeholder centred studies, to develop robust strategic plans. An affiliate coordinator for wheelchair provision in less resourced settings supported this process. Results : Diversity between the two-affiliate sites was evident, influencing value placed within both societies towards equality and participation. Common components to address included: advocacy; wheelchair service infrastructure; capacity building; education; training and research. Research process facilitation supported by affiliate coordinator is important. Conclusion : Understanding contextual dimensions, which sharp a countries wheelchair service, is essential. Member states should take action by conducting in-country wheelchair sector analysis, to create wheelchair provision strategies for sustainable development, to meet personal posture and mobility needs, primary for daily living, as a basic human right. Implications for rehabilitation: Understanding the complexity of providing appropriate wheelchairs within different countries is essential to meet the diverse needs of citizens. Conducting situational analysis of the wheelchair sector involving key stakeholders in the process is important to understand different perspectives and develop strategic priorities towards sustainable development. Producing context specific wheelchair sector reports and strategic plans strengthens the evidence base when informing governments regarding the importance of developing sustainable wheelchair provision infrastructures. The affiliate coordinator role is important to support affiliates to produce robust documentation that clearly and objectively outlines the wheelchair sector issues and plans, to provide solutions.